A Survey on Organizational Choices for Microservice-Based Software Architectures - Ünlü, Hüseyin; Bilgin, Burak; Demirörs, Onur; Demirörs, Onur (TÜBİTAK, 2022)
During the last decade, the demand for more flexible, responsive, and reliable software applications increased exponentially. The availability of internet infrastructure and new software technologies to respond to this demand led to a new generation of applications. As a result, cloud-based, distributed, independently deployable web applications working together in a microservice-based software architecture style have gained popularity. The style has been a common practice in the industry and successfully utilized by companies. Adopting this style demands software organizations to transform their culture. However, there is a lack of research studies that explores common practices for microservices. Thus, we performed a survey to explore the organizational choices on software analysis, design, size measurement, and effort estimation when working with microservices. The results provide a snapshot of the software industry that utilizes microservices. We provide insight for software organizations to transform their culture and suggest challenges researchers can focus on in the area.
Keywords: Microservice architecture; Practitioner survey; Software analysis